Kegiatan Penapisan Kadar Air dan Minyak Kulit Sebagai Deteksi Dini Kulit Kering di SMAN 75, Jakarta Utara - Sidarta, Erick; Gunaidi, Farell Christian; Destra, Edwin; Fadhila, Arni Ismi (jurnal ABDIMAS Indonesia, 2024)
Skin hydration is critical to maintaining healthy skin, as the skin functions as a physical barrier against external environmental factors such as pathogen invasion, UV radiation, chemical exposure, and mechanical trauma. This activity highlights the importance of early detection of skin hydration levels to prevent conditions such as dry skin with a Plan-Do-Check-Action (PDCA) approach. Effective strategies such as regular use of moisturizer, a healthy diet, increased fluid intake, a gentle skin cleansing routine, and regular monitoring using a skin analyzer are important to maintain healthy skin. Community education and screening demonstrated a positive impact on skin hydration awareness and practice, emphasizing the importance of hydration in improving skin barrier function and overall quality of life.